2016
DOI: 10.1038/srep26832
|View full text |Cite
|
Sign up to set email alerts
|

Dispersive Non-Geminate Recombination in an Amorphous Polymer:Fullerene Blend

Abstract: Recombination of free charge is a key process limiting the performance of solar cells. For low mobility materials, such as organic semiconductors, the kinetics of non-geminate recombination (NGR) is strongly linked to the motion of charges. As these materials possess significant disorder, thermalization of photogenerated carriers in the inhomogeneously broadened density of state distribution is an unavoidable process. Despite its general importance, knowledge about the kinetics of NGR in complete organic solar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
81
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 56 publications
(84 citation statements)
references
References 56 publications
3
81
0
Order By: Relevance
“…In order to elucidate the role of the pathways on the free carrier generation, we performed TDCF experiments as a function of the electric field and temperature with excitation at different photon energies. The experimental details on TDCF have been described elsewhere . In short, the device is excited with a short laser pulse (≈5 ns) while being held at a given pre‐bias ( V pre ).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In order to elucidate the role of the pathways on the free carrier generation, we performed TDCF experiments as a function of the electric field and temperature with excitation at different photon energies. The experimental details on TDCF have been described elsewhere . In short, the device is excited with a short laser pulse (≈5 ns) while being held at a given pre‐bias ( V pre ).…”
mentioning
confidence: 99%
“…This is because SCLC is by the motion of dark‐injected charges, which are situated in the tail of the DOS right from the beginning, while photogenerated charges may initially occupy states near the center of the DOS. We have recently shown that studies of dispersive recombination with TDCF provide direct access to the thermalization properties of photogenerated carriers in the actual device . For this measurement, the device is held at a given V pre , typically close to the maximum power point, while the delay time ( t del ) is now varied from few ns to µs (see Note S4, Supporting Information).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Neher et al have used a model to determine a potential field‐dependence of the bimolecular recombination coefficient itself . For each value of V pre , a series of TDCF experiments with a variation of the delay time t d is performed.…”
Section: Measurement Principle Of Tdcfmentioning
confidence: 99%
“…Neher et al have used a model to determine a potential fielddependence of the bimolecular recombination coefficient itself. [12,17,31] For each value of V pre , a series of TDCF During the delay charge carriers may either recombine or be extracted at the contacts. The latter are referred to as n pre in the following and charge carriers extracted after switching to the collection bias V coll are referred to as n coll .…”
Section: Apparent Voltage-dependence Of the Bimolecular Recombinationmentioning
confidence: 99%